2019
DOI: 10.1051/0004-6361/201935830
|View full text |Cite
|
Sign up to set email alerts
|

Physics-based model of the adaptive-optics-corrected point spread function

Abstract: Context. Adaptive optics (AO) systems greatly increase the resolution of large telescopes, but produce complex point spread function (PSF) shapes, varying in time and across the field of view. The PSF must be accurately known since it provides crucial information about optical systems for design, characterization, diagnostics, and image post-processing. Aims. We develop here a model of the AO long-exposure PSF, adapted to various seeing conditions and any AO system. This model is made to match accurately both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
1
54
0
Order By: Relevance
“…The estimation of r 0 thanks to telemetry data is usually not perfectly accurate and the Fried parameter is often overestimated. However, it has been shown that an AO system can be characterised well to correct for this offset (Fétick et al 2019).…”
Section: Obtaining the Residual Psdmentioning
confidence: 99%
“…The estimation of r 0 thanks to telemetry data is usually not perfectly accurate and the Fried parameter is often overestimated. However, it has been shown that an AO system can be characterised well to correct for this offset (Fétick et al 2019).…”
Section: Obtaining the Residual Psdmentioning
confidence: 99%
“…This model was originally introduced by Fétick et al (2019b) and validated on SPHERE/ZIMPOL and MUSE NFM data. In order to increase the range of applicability of such a model, we upgraded it by including (i) the model of the Apodized Lyot Coronagraph (APLC, Soummer (2005)) used on SPHERE (focal-plane mask not considered) (ii) additional degrees of freedom to adjust static aberrations over a specific modal basis, which can be Zernike modes described on the pupil, tip-tilt and piston modes for each pupil area delimited by the spiders so as to describe the so-called LWE or piston modes for each pupil segment (Laginja et al 2019;Leboulleux et al 2018;Ragland 2018).…”
Section: Psf Modelmentioning
confidence: 99%
“…where D AO , B AO , and W AO are the residual phase structure function, autocovariance function, and PSD respectively, k is the spatial frequencies vector and F [x] is the 2D Fourier transform of x. In Fétick et al (2019b), the PSD is described as a split function to separate the AO-corrected spatial frequencies from the uncorrected frequencies that follow a Kolmogorov's −11/3 power law (Kolmogorov 1941)…”
Section: Psf Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in order to provide evidence that PRIME is a good solution for PSF-fitting problems post-AO, we have also compared herein results with a Moffat-fitting using the exact same model-fitting process. The Moffat function was defined over 7 parameters (Fétick et al 2019) to allow fitting of asymmetric PSF shape. We report in Fig.…”
Section: Maximizing the Utmost Psf-r Performancementioning
confidence: 99%